PENGARUH MODEL PEMBELAJARAN GAME BASED LEARNING DALAM PEMBELAJARAN IPAS MATERI KEANEKARAGAMAN HAYATI TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS IV DI SD GMIT OEBOBO KOTA KUPANG - fallo, odiliadiana; R. Koroh, Taty; Triastuti R. A. Ratu, Kurniayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determinate the effect of the Game Based Learning (GBL) model on the learning outcomes of fourth-grade students on biodiversity material at SD GMIT Oebobo, Kupang City. This research used a quantitative approach with a preeksperimental one group pretest-posttest design. The sample consisted of 18 students selected using a saturated sampling thechnique. Instruments used included test (pretest and posttest), observations, and documentations. The validity of the instruments was assessed through expert judgement, while reliability was tested using Cronbach’s Alpha, resulting in a velue of 0,717. Data alalysis using SPSS showed that the data were normally distributed and homogeneous. The paired sample T-Test resulted in a significance velue of 0,000 < 0,005, indicating a significant difference between pretest and posttest scores. These results prove that the Game Based Learning model has a positive impact on student’s learning outcomes. The model not only improves academic performance but also enhances student engagement and motivation during the learn process. Therefore, Game Based Learning can be use as an innovative alternative teaching model in primary schools.